Why Am I Willing to Speak Up? The Impact of Spiritual Leadership on Employee Voice Behavior - Yang, Xuhua; Meng, Yuchen; Qiu, Yong; Feng, Yaqian (Frontiers in Psychology, 2019)
The sustainability of organizations highlights the significance of inspiring employees, especially their inner lives or spiritual identities, and leaders play a vital role. Consistent with social cognitive theory, the purpose of this paper is to explore the linking mechanisms and conditional processes underlying the relationship between spiritual leadership and employee voice behavior. Three-wave survey data were collected from 366 full-time employees and their line managers, and a moderated mediation analysis was performed. The results show that career success expectation fully mediates the relationship between spiritual leadership and employee voice behavior. Additionally, felt obligation is found to indirectly strengthen the effect of spiritual leadership on employee voice behavior via career success expectation. In light of the results, practical implications are provided for managers and future researchers to enhance the sustainability of organizations.